Thermal performance of a novel helically coiled oscillating heat pipe (HCOHP) for isothermal adsorption: an experimental study - Yeboah, S.K.; Darkwa, Jo (Elsevier, 2018)
Helically Coiled Oscillating Heat Pipes (HCOHPs) have been designed and tested under laboratory conditions to investigate their potential to achieve isothermal adsorption when integrated with a cylindrical solid desiccant packed bed system. The HCOHPs fabricated out of copper, are essentially single turn closed loop oscillating heat pipes with their evaporator and condenser sections helically coiled. They were charged with ethanol, methanol and deionized water respectively at approximately 60% volume fill ratio and tested by slotting through their helically coiled evaporators an empty cylindrical copper vessel which allowed hot air to be blown through at various heat loads to ascertain their thermal performances.